Averroism and the Evolution of Jesuit Educational Missions in Indonesia: A Historical-Philosophical Review - Vachruddin, Vrisko Putra; Mahfudloh, Ririn Inayatul; Asror, Moh; Trisnandyah, Ayzha Mayang (LPPM IAIN Kudus, 2025)
The Averroism movement emerged as a form of support and resistance from European thinkers who followed Ibn Rushd’s way of thinking against church authority. This movement opposed the indoctrination by church authorities that restricted freedom of thought. Church authorities assumed that church doctrine was true and should not contradict it. The impact of the massive Averroism movement caused the loss of church authority accompanied by internal conflicts that hit the church camp. To strengthen the doctrine and faith of Catholics, Pope Paul III ordered Ignatius Loyola to establish schools, colleges, and seminaries which were institutions engaged in education known as the Society of Jesus. This study seeks to review and deepen the historical and philosophical study of Averroes’ movement in the establishment and development of the Society of Jesus in Indonesia. This study uses a literature review research method with two approaches, namely the historical research approach and the philosophical approach. The results of the study stated that there were two factors relating the Averroism movement to the development of the Society of Jesus education in Indonesia,: The loss of church authority due to opposition to the Averroism movement and Efforts to indoctrinate through education about Catholic teachings and understanding through the Society of Jesus. This study emphasizes that the establishment and development of the Society of Jesus in Indonesia cannot be separated from the influence of the Averroism which is expressed in thoughts about freedom of thought and the indoctrination of education.